Conserving Artistic Expression and Cultural Education through the Gending Sriwijaya Dance - Naomi Diah Budi Setyaningrum; Hartono Hartono; Malarsih Malarsih; Widodo Brotosejati (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Gending Sriwijaya dance, a classical performance from South Sumatra, holds deep cultural, historical, and educational significance. However, its presence in formal education remains limited, raising concerns about cultural sustainability and the weakening of traditional identity among younger generations. This study investigates how Gending Sriwijaya can be integrated into educational contexts to promote cultural conservation, artistic expression, and character development. This qualitative study employed a combined approach of library research and limited field-based inquiry, including semi-structured interviews and participant observation. Data were sourced from academic literature, cultural policy documents, and direct engagement with dance educators and practitioners at Universitas PGRI Palembang. Thematic analysis and data reduction techniques were used to interpret both documentary and empirical findings. The findings reveal that Gending Sriwijaya serves as a powerful medium for transmitting cultural values such as spirituality, hospitality, ecological awareness, and discipline. The dance’s symbolic movements and properties convey rich semiotic meanings that can support progressive learning goals. Its inclusion in university curricula fosters bodily coordination, creativity, cultural pride, and social cooperation among students. Integrating Gending Sriwijaya into educational programs not only preserves regional heritage but also aligns with progressive education principles that emphasize experiential and culturally relevant pedagogy. This study recommends structured curriculum development, teacher training, and institutional collaboration to ensure the dance’s sustainability and educational impact.